Extending the Applicability of Probabilistic Management Planning and Control Models. - Buzby, Stephen L. (The Accounting Review, 1974)
Presents information on a study which applied probabilistic models to management planning and control in accounting. Mathematical expression of nonprobabilistic approach to management planning and control; Problem with the traditional nonprobabilistic approach and probabilistic approach.